SIGNIFICANCE OF THE CALCIUM DEFICIT IN PEDIATRICS AND WAYS TO CORRECT IT - O.A. Gromova ("Paediatrician" Publishers LLC, 2007)
Calcium takes an active part in provision and development of the motion function (tractions, transmission of the neural impulse, muscle reactions to the neural excitement, change of the hormone activity, realizing together with adenylate cyclase). But no less important is the calcium role in participation of the supporting tissue buildup, organization of the integral child's skeletal system, in which there is 99% of the body calcium. This is a sort of depot, in which the element is in the dynamic equilibrium with its level in blood. The skeletal system acts as a buffer to support the stable level of the calcium circulation in the course of the entire life cycle. The calcium deficit among children should fully be treated, frequently conducting therapy of the accompanied pathology of the gastrointestinal tract, liver and intestinal dysbiosis. We should exclude the hereditary pathology of the calcium exchange. For the usual growth of the human body and prevention of the senile osteoporosis, the necessary amount of calcium consumption should be provided from the very childhood of a person. For the prevention and treatment of the calcium deficit among children, we use specific calcium medications together with phosphorus, magnesium, microelements and vitamins tested in clinical practice and approved by the union of pediatricians of Russia.Key words: calcium, deficit of major mineral elements, treatment, prevention, children.